Study of Fish Marketing System of Daryapur, District Amravati (Maharashtra) (International Journal of Food and Nutritional Sciences, 2022)
This study was conducted on marketing system of Daryapur to study the types of available fresh water fish species in the market, the water resources for fish catching, the market's state, its facilities, cold chain, cleanliness, the major species sold, and its price structure. The 14 different fish species were sold in this market. The most commonly sold species are Catla, Rohu, Mrigal, Murral, Poshti, Suwa, Ktarna, Pankaj, Gobi, Chala Chanda, Singhade etc. The most important fish during this study Daryapur fish market fish species including Catla, Rohu, Murral, Mrigal were sold in huge quantities in market. Most of the fish seller catches the local fishes from the different resources like Purna river, Chandrabhaga river, and small water reservoir nearby Daryapur and they sell the fish in the market. The price fluctuation in fishes is very high because of the uncertain of catch production and sort run supply. Fish vendors in Daryapur fish market do not have proper refrigeration and freezing facilities. They rely on ice for fish storage. Hygiene conditions at the Daryapur fish market, which was the subject of the study, were very poor. Fish were offered for sale on plastic sheets, plastic sacks, and open flour. Cutting knives and platforms were not properly stored and often lay on open ground full of dirt, mud and dust